1979
DOI: 10.1111/j.1469-7998.1979.tb03401.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the vascular system of the head and neck of the helmeted guineafowl Numida meleagris

Abstract: The vascular anatomy of the head and neck of eight adult helmeted guineafowl (Numida meleagris) was investigated by latex injections and dissection, resin casting, and lipidol injections and X‐ray photography. The vascular anatomy of these regions is similar to that of the domestic fowl Gallus domesticus, the main differences being in the helmet, wattle and cere vascularization, and the presence of a nape‐cheek rete in N. meleagris. It is postulated that five vascular arrangements in the head and neck are impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…According to De Vriese (1905), the cerebral carotid artery divided itself beside the hypophysis into two branches, a large caliber rostral branch and a middle caliber caudal branch (Westpfahl 1961, Richards 1967, Crowe & Crowe 1979, Midtgard 1984, Campos 1987, Campos et al 1995, and the same was found in turkey. For Kitoh (1962), studying in Gallus, observed that the rostral and caudal branches had almost the same caliber.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…According to De Vriese (1905), the cerebral carotid artery divided itself beside the hypophysis into two branches, a large caliber rostral branch and a middle caliber caudal branch (Westpfahl 1961, Richards 1967, Crowe & Crowe 1979, Midtgard 1984, Campos 1987, Campos et al 1995, and the same was found in turkey. For Kitoh (1962), studying in Gallus, observed that the rostral and caudal branches had almost the same caliber.…”
Section: Discussionmentioning
confidence: 83%
“…The internal carotid arteries proceeded cranium--medially in the ventral median line of the neck running along the cervical carotid canal, and close to the base of the cranium each internal carotid artery projected the external carotid artery and the cerebral carotid artery. Crowe & Crowe (1979), in Helmeted guineafowl (Numida meleagris), observed that the common carotid arteries were divided into two equal branches, the internal and external carotid arteries. For these authors, the internal carotid artery was divided into two equal vessels at the base of the cranium, an external ophthalmic artery, of larger caliber, and a cerebral carotid artery, of smaller caliber.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations